2023
DOI: 10.3389/fpubh.2023.1192099
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 intake is associated with liver disease protection

Abstract: BackgroundNon-alcoholic fatty liver disease (NAFLD) and alcoholic liver disease are among the most common liver diseases worldwide, and there are currently no Food and Drug Administration (FDA)-approved treatments. Recent studies have focused on lifestyle changes to prevent and treat NAFLD. Omega-3 supplementation is associated with improved outcomes in patients with chronic liver disease. However, it is unclear whether Omega-3 supplementation can prevent the development of liver disease, particularly in indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…(mean difference=0.50±0.16, p<0.02). P. frutescens seed oil is distinguished for its rich content of plant-derived omega-3 fatty acids, predominantly alpha-linolenic acid [13]. Such fatty acids are deemed essential, necessitating dietary acquisition due to the body's inability to synthesize them [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(mean difference=0.50±0.16, p<0.02). P. frutescens seed oil is distinguished for its rich content of plant-derived omega-3 fatty acids, predominantly alpha-linolenic acid [13]. Such fatty acids are deemed essential, necessitating dietary acquisition due to the body's inability to synthesize them [14].…”
Section: Resultsmentioning
confidence: 99%
“…A previous study in 2017 reported that omega-3 exhibited antiinflammatory effects compared to diclofenac. Omega-3 was found to function as a natural anti-inflammatory agent against osteoarthritis [13].…”
Section: Resultsmentioning
confidence: 99%
“…Studies involving humans also show promising results (Table 2). An analysis of British Biobank data by Vell et al showed that the regular consumption of n-3 fatty acids was associated with a significant reduction in the risk of developing liver disease, especially in the case of MASLD [121]. In a study by Cansanção et al, oral n-3 supplementation in the form of fish oil capsules (503 mg DHA and 103 mg eicosapentaenoic acid (EPA)) three times daily for 6 months showed a significant reduction in liver fibrosis.…”
Section: Omega-3 Polyunsaturated Fatty Acids (Pufas)mentioning
confidence: 99%
“…This approach was based on the possible therapeutic effect of polyunsaturated FAs. However, in-vivo and clinical studies produced conflicting results [37,38 ▪ ]. Another method is intervening in the proteome surrounding the lipid droplet or targeting proteins responsible for lipid droplet growth and degradation.…”
Section: Therapeutic Potential and Strategiesmentioning
confidence: 99%